Analisis Berita Acara Pemeriksaan Pengeroyokan - Samara, Finsensius; Saputra, Eka Cahyo; Carmelita, Carita Sophi; Pinandhita, Neyska Dealova; Lewotan, Clemensia Nova (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The Investigation Report (BAP) is a crucial tool in the enforcement of Indonesian criminal law, as it records detailed statements from victims, witnesses, and suspects to establish the chronology of events and their relationship to legal norms. This study analyzes the BAP related to the alleged assault on March 5, 2023, in Nanga Mbaur Village, East Manggarai Regency, where two or more people attacked the victim, potentially causing injury or death. Through a normative juridical approach, this study reveals the strength of BAP evidence in proving the criminal elements of assault in accordance with Article 170 of the Criminal Code (KUHP), as well as its implications for the judicial process. The findings emphasize the need for accuracy and completeness of BAP to ensure restorative justice at the investigation level.